Cyber and traditional peer victimization: Examining unique associations with children's internalizing difficulties. (October 2018) - Williford, Anne; Orsi, Rebecca; DePaolis, Kathryn J.; Isen, Debbie
Abstract: Peer victimization leads to a number of negative developmental outcomes. Although many studies have explored cyber victimization impacts in adolescent samples, few have analyzed unique negative consequences in relation to younger children. To that end, the purpose of the present study is to examine the associations between cyber victimization and internalizing problems, alone and in combination with traditional victimization. Using a sample of 3rd through 5th grade students, structural equation modeling results reveal that traditional victimization was significantly related to depressive symptoms, anxiety symptoms, and lower self-esteem; however, cyber victimization was not related to any of these outcomes of interest. Several gender and grade level differences were also found. Although a notable portion of the sample reported exposure to cyber victimization, traditional forms of victimization were more common. Implications for school-based prevention and intervention efforts are discussed. Highlights: Few studies have analyzed the unique negative consequences of cyber and traditional victimization among younger children. Younger children are accessing interactive communication technologies (ICTs) and mobile devices at rapidly growing rate. We examine cyber victimization and internalizing problems, in combination with traditional forms, among 3 rd -5 th graders. Results reveal that traditional victimization was significantly associated with depressive symptoms, anxiety symptoms, and lower self-esteem. However, cyber victimization was not significantly related these outcomes of interest. Although a notable portion of the sample reported exposure to cyber victimization, traditional forms were more common.